Estimating outdoor advertising media visibility with voxel-based approach. (October 2017) - Chmielewski, Szymon; Tompalski, Piotr
Highlights: The 3D fuzzy approach to visibility modeling is presented. The advertisement billboard visibility model is elaborated. The influence of various voxelization methods on ground-truth visibility models accuracy is described. A voxel volume adjusted to the post-spacing interval provides the highest accuracy of visibility models.